Rift Valley Fever Virus Is Lethal in Different Inbred Mouse Strains Independent of Sex - Cartwright, Haley N.; Barbeau, Dominique J.; McElroy, Anita K. (Frontiers in Microbiology, 2020)
Rift Valley fever virus (RVFV) is a zoonotic arbovirus affecting humans and livestock in Africa and the Arabian Peninsula. The majority of human cases are mild and self-limiting; however, severe cases can result in hepatitis, encephalitis, or hemorrhagic fever. There is a lack of immunocompetent mouse models that faithfully recapitulate the varied clinical outcomes of RVF in humans. However, there are easily accessible and commonly used inbred mouse strains that have never been challenged with wild-type RVFV. Here, RVFV susceptibility and pathogenesis were evaluated across five commonly used inbred laboratory mouse strains: C57BL/6J, 129S1/SvlmJ, NOD/ShiLtJ, A/J, and NZO/HILtJ. Comparisons between different mouse strains, challenge doses, and sexes revealed exquisite susceptibility to wild-type RVFV in an almost uniform manner. Never before challenged NOD/ShiLtJ, A/J, and NZO/HILtJ mice showed similar phenotypes of Rift Valley fever disease as previously tested inbred mouse strains. The majority of infected mice died or were euthanized by day five post-infection due to overwhelming hepatic disease as evidenced by high viral RNA loads in the liver. Mice surviving past day six across all strains succumbed to late-onset encephalitis. Remarkably, sex was not found to impact survival or viral load and showed only modest effect on time to death and weight loss for any of the challenged mouse strains following RVFV infection. Regardless of sex, these inbred mouse strains displayed extreme susceptibility to wild-type RVFV down to one virus particle.